SISTEM PENDUKUNG KEPUTUSAN KLASIFIKASI BERAS TERBAIK MENGGUNAKAN METODE GROUP ALGORITHM PROGRAMMING BERBASIS WEB - Mirna Khairana (Yayasan Sagita Akademia Maju, 2024)
The system that overcomes this problem is the best rice classification decision support system at Perum Bulog, Pidie Regency and with this system it can later help determine the suitability of the best rice classification needed by consumers. The method used is Group Algorithm Programming (GAP), the process of calculating this GAP method uses GAP analysis by finding the best rice classification profile value that has a profile as close as possible to the profile value desired by consumers. This application system is dynamic in terms of adding and subtracting the need for the criteria that are the reference in the assessment. The result of this process is the ranking of the best rice classification profile values that will be used as recommendations for making the best rice classification decision. Classification of the best rice is a special problem that is often encountered in Perum Bulog, for that we need the right decision- making system in determining the best rice classification, so that the best rice distribution service can be achieved optimally and minimize the factors that will affect it. become an obstacle in the classification of the best rice in Indonesia. Bulog of Pidie Regency.